DOCK5 functions as a key signaling adaptor that links FcεRI signals to microtubule dynamics during mast cell degranulation - Ogawa, Kana (The Rockefeller University Press, 2014)
Mast cells play a key role in the induction of anaphylaxis, a life-threatening IgE-dependent allergic reaction, by secreting chemical mediators that are stored in secretory granules. Degranulation of mast cells is triggered by aggregation of the high-affinity IgE receptor, FcεRI, and involves dynamic rearrangement of microtubules. Although much is known about proximal signals downstream of FcεRI, the distal signaling events controlling microtubule dynamics remain elusive. Here we report that DOCK5, an atypical guanine nucleotide exchange factor (GEF) for Rac, is essential for mast cell degranulation. As such, we found that DOCK5-deficient mice exhibit resistance to systemic and cutaneous anaphylaxis. The Rac GEF activity of DOCK5 is surprisingly not required for mast cell degranulation. Instead, DOCK5 associated with Nck2 and Akt to regulate microtubule dynamics through phosphorylation and inactivation of GSK3β. When DOCK5–Nck2–Akt interactions were disrupted, microtubule formation and degranulation response were severely impaired. Our results thus identify DOCK5 as a key signaling adaptor that orchestrates remodeling of the microtubule network essential for mast cell degranulation.